Pengaruh Kurikulum Merdeka Belajar Terhadap Kreativitas Belajar PAK Siswa Kelas VII SMP Negeri 4 Laguboti Kabupaten Toba Tahun Pembelajaran 2022/2023 - Natasya Silaban; Tianggur Napitupulu; Rida Gultom; Malani Simanungkalit; Limmarten Simatupang (LPPM Politeknik Pratama, 2023)
The purpose of this study was to determine the positive and significant effect of Merdeka Belajar Curriculum on students' PAK learning creativity in class VII of SMP Negeri 4 Laguboti, Toba Regency for the 2022/2023 Learning Year. The research method used in this research is quantitative method with descriptive statistics approach. The population is the entire VII grade of SMP Negeri 4 Laguboti Toba Regency for the 2022/2023 Learning Year, totaling 190 people and a sample of 57 people was determined using random sampling technique. Data were collected with a positive closed questionnaire of 32 items. The results of data analysis show that there is a positive and significant effect of Merdeka Belajar Curriculum on students' PAK learning creativity in class VII of SMP Negeri 4 Laguboti Toba Regency for the 2022/2023 Learning Year: 1) Analysis requirements test: a) positive relationship test obtained rxy value = 0.422> rtable (α = 0.05, IK = 95%, n = 57) = 0.254 thus it is known that there is a positive relationship between variable X and variable Y. b) Significant relationship test obtained tcount = 3.813> ttable (α = 0.05, dk = n-2 = 55) = 2.000 thus there is a significant relationship between variable X and variable Y. 2) Effect test: a) Regression equation test, obtained regression equation Ŷ=15.56+0.93X. b) Regression determination coefficient test (r²)=17.8%. Thus Ha is accepted and H0 is rejected.